The agricultural systems of the world : - Grigg, David B. (Cambridge University Press, 1974)
This book is about the prevalent characteristics and distribution of the major agricultural systems of the world - shifting cultivation, wet rice cultivation, pastoral nomadism, Mediterranean agriculture, mixed farming, dairying, plantations, ranching and large-scale grain production.